Simulate Three Way Catalyst Performance on Spark Injection Engine Using Ethanol-Gasoline Blend Fuel E10-E20 - Nguyen, The Luong (Old Journal, 2018)
This paper simulated Three Way Catalysts (TWC) performance on spark injection engine (SI. Engine)) using ethanol-gasoline blend fuel E10-E20, the simulation was done on AVL-Boost sorfware, the emperimetns were carried on CD 20" bench to determine the initial and boundary conditions. The results showed that, the error between simulation and experiment results were less than 5%. The simulation results on Sl. Engine with three kind of fuel Ron95 (E0), E10, E20 also showed that, the three way catalysts performance when using ethanol-gasoline blend fuel E0, E10, E20 were same trend, when throttle increased from 25% to 100%, CO, HC, NOx treatment perfomance decreased strongly, the specially at throttle 100%, CO and HC treatment perfomance decreased 1% rest. When the speed increased from 20 km/h to 80 km/h, CO, HC and f NOx treatment perfomance were not clear trend, the CO, HC and f NOx treatment perfomance value varied more or less than 10%. When using E10, E20, CO, HC treatment perfomance were higher than gasoline E0, while NOx treatment perfomance was lower, the averagre CO and HC treatment perfomance increased respectively 3,2% and 4,15% with E10, 5,25% and 6,2% with E20, the the averagre NOx treatment perfomance decreased respectively 6,2% with E10 and 7,7% with E20.